ChemInform Abstract: Hypervalent Iodine Mediated Alkene Difunctionalization of Vinylphenols: Diastereoselective Synthesis of Substituted Indoles and Indolizines. Issue 32 (August 2015) - Zhang, Kai; Wang, Hang; Zheng, Jingfeng; Yu, Lei; Ding, Hanfeng
Abstract The title reaction allows the facile synthesis of 3‐substituted indoles and 2‐substituted indolizines with good yields and high diastereoselectivities.